Hukum sebagai Alat Ketertiban atau Alat Keadilan: Tinjauan Kritis terhadap Praktik Penegakan Hukum di Indonesia - Yudith Bana; Virginia Usfunan; Efatha F.B. Duarte (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
The debate over whether law functions primarily as an instrument of social order or as a means of achieving substantive justice remains central to contemporary legal discourse in Indonesia. This article critically examines law enforcement practices by analyzing how the dominance of legal-formalistic and procedural approaches has gradually displaced substantive justice in favor of administrative order and institutional stability. Employing a socio-legal and legal-philosophical framework, the study demonstrates that procedural compliance frequently produces an illusion of justice, while legal processes themselves operate as mechanisms of disproportionate punishment, particularly for socially and economically vulnerable groups. The emphasis on procedural authority and discretionary power within criminal case processing reinforces asymmetric power relations and obscures the ethical objectives of law. These arguments are supported by critical scholarship on procedural justice, power dynamics in legal decision-making, and the concept of substantive justice grounded in legal pluralism and Pancasila-based legal values. The article concludes that without a paradigmatic reorientation toward context-sensitive substantive justice, law enforcement in Indonesia risks remaining an instrument of social order rather than a corrective mechanism for structural injustice. Keywords: law enforcement; substantive justice; legal order; socio-legal studies Abstrak Perdebatan mengenai fungsi hukum sebagai alat ketertiban atau sebagai sarana keadilan substantif tetap menjadi isu sentral dalam praktik penegakan hukum di Indonesia. Artikel ini mengkaji secara kritis bagaimana dominasi pendekatan legal-formalistik dan prosedural dalam sistem peradilan pidana Indonesia telah menggeser orientasi hukum dari pencapaian keadilan substantif menuju stabilisasi ketertiban administratif. Berangkat dari pendekatan sosio-legal dan analisis filosofis hukum, kajian ini menunjukkan bahwa kepatuhan prosedural sering kali menghasilkan ilusi keadilan, sementara proses hukum itu sendiri berfungsi sebagai bentuk penghukuman yang tidak proporsional, khususnya terhadap kelompok rentan. Praktik penegakan hukum yang menitikberatkan pada kepastian normatif dan kewenangan diskresioner aparat memperkuat relasi kuasa yang timpang serta mengaburkan tujuan etik hukum. Temuan konseptual ini diperkuat oleh kajian mengenai keadilan prosedural, dinamika kekuasaan dalam pengambilan keputusan hukum, serta gagasan keadilan substantif berbasis pluralisme hukum dan nilai Pancasila. Artikel ini menegaskan bahwa tanpa reorientasi paradigma menuju keadilan substantif yang kontekstual dan sensitif terhadap realitas sosial, hukum di Indonesia berpotensi terus berfungsi sebagai instrumen ketertiban semata, alih-alih sebagai alat koreksi ketidakadilan struktural dalam masyarakat. Keyword: penegakan hukum; keadilan substantif; ketertiban hukum; sosio-legal